Computing Water Requirement of Groundnut - Reddy, P Ramachandra (Annals of Arid Zone, 2016)
Water requirement of groundnut was computed based on the four prediction formulae recommended by FAO group of scientists. It ranged from 281.48 mm to 433.59 mm. The data were compared with the data from actual field experimentation. The values from modified Penman method were more closer to the field experimental values indicating usefulness of modified Penman method in computing water requirements of crops.